A.07 Genomics of atypical dyskinetic cerebral palsy – opportunities for improved diagnosis and management. (2nd June 2017) - Goez, H; Matthews, A; Al Jabri, B; Blydt-Hansen, I; Andersen, J; Tarailo-Graovac, M; Drogemoller, B; Shyr, C; Lee, J; Ghani, A; Sinclair, G; Ross, C; et al.
Abstract : Background: Cerebral palsy (CP) is a debilitating disorder (1). Based on neuromotor impairments it is divided to spastic, dyskinetic and ataxic types (2). Inborn Errors of Metabolism (IEMs), monogenic and chromosomal disorders mimic CP (3). We aimed to identify causal genetic variants in patients with atypical dyskinetic CP in whom known IEMs were ruled out. Timely diagnosis is essential for proper management, especially in conditions that mimic CP and are treatable.Methods: We enrolled 23 patients with unexplained atypical dyskinetic CP, for whole exome sequencing. Variants were filtered against public and in-house databases to identify variants predicted as damaging ( in silico tools and ACMG criteria). We applied a virtual gene panel of known and suspected CP and movement disorder genes and investigated each sample.Results: The participants presented with symptoms including: spasticity, dystonia, choera-athetosis, ataxia and cognitive delays. We identified 23 diagnoses: 13 dominant, 6 recessive and 4 X-linked. 12 patients had movement disorders. In 4, the diagnoses enabled targeted treatment (neurotransmitter supplements in Unverricht Lundborg diseases (CSTB) and PAK3 deficiency, deep brain stimulation in GNAO1 deficiency, medical diet in Glutaric Aciduria (GCDH).Conclusions: Whole Exome Sequencing contributes to establishing diagnosis in patients with atypical dyskinetic CP resulting in precision medicine and improved health outcomes.